Bran characteristics influence the quality of whole‐wheat pancakes and baking powder biscuits. Issue 4 (29th April 2019) - Ma, Fengyun; Lee, Yu Young; Palmquist, Debra E.; Baik, Byung‐Kee
Abstract: Background and objectives: Bran characteristics differ widely among wheat varieties and influence the quality of whole‐wheat products. The objective of this study was to identify bran characteristics that influence the quality of whole‐wheat pancakes and baking powder biscuits made from whole‐wheat meals (WWMs), which were blends of the brans of 17 soft red winter wheat varieties and two wheat flours. Findings: Pancake diameters of 34 WWMs ranged from 106.6 to 116.0 mm. Biscuit height and shape factor (SF) of 34 WWMs ranged from 28.8 to 34.2 mm and 1.10–1.24, respectively. Bran protein content showed positive relationships with pancake diameter and biscuit height for both wheat flours blended with brans. Water‐retention capacity, free phenolics, and water‐extractable arabinoxylan contents of bran exhibited significant relationships with pancake diameter and biscuit SF in WWMs for only one wheat flour. Conclusions: Whole‐wheat meals containing brans of high protein content produced pancakes of comparable diameter to those made with wheat flour. WWMs containing bran of high protein and soluble dietary fiber (DF) contents, and low arabinoxylan and insoluble DF contents produced biscuits with intermediate‐to‐high height and low‐to‐intermediate SF. Significance and novelty: The results identify bran characteristics desirable for making whole‐wheat pancakes and biscuits.